Pesantren di Tengah Arus Modernisasi Pendidikan: Analisis Kritis terhadap Misi Pencetakan Ulama - Iit Supriatin; Redi Rustandi; Neneng Nia Kurniasih (PT. Student RIhlah Indonesia, 2026)
This study aims to critically examine how educational modernization affects the sustainability of pesantren’s mission in producing ulama in contemporary Indonesia. Employing a qualitative analytical approach based on library research, the study analyzes educational policy documents, official statistical data from the past five years (2020–2024), and relevant previous studies. Data are examined through critical content analysis and policy discourse analysis to uncover underlying structural and ideological dynamics. The findings reveal that the modernization of pesantren education produces ambivalent consequences. On the one hand, modernization enhances institutional legitimacy, expands access to state funding, and improves graduates’ social mobility. On the other hand, the dominance of the national curriculum and vocational orientation tends to reduce the intensity of classical Islamic learning, thereby weakening pesantren’s traditional function as institutions for the systematic production of ulama grounded in scholarly transmission (sanad). Within this context, the study identifies the emergence of a new typology of “hybrid ulama,” reflecting a negotiated synthesis between pesantren’s classical scholarly tradition and contemporary competency demands. The novelty of this study lies in its application of a critical education policy perspective to reveal power relations among the state, pesantren, and the market in the post–Pesantren Law era. Practically, the findings underscore the need for more affirmative and flexible education policies that recognize the distinctive character of pesantren, ensuring that modernization strengthens rather than dilutes their foundational mission in producing Islamic scholars who remain relevant to contemporary challenges without losing their classical intellectual roots.